Answer:
G(-1) = -2
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
<u>Algebra I</u>
Functions
Step-by-step explanation:
<u>Step 1: Define</u>
<em>Identify</em>
G(x) = 5x + 3
<u>Step 2: Evaluate</u>
- Substitute in <em>x</em> [Function G(x)]: G(-1) = 5(-1) + 3
- Multiply: G(-1) = -5 + 3
- Add: G(-1) = -2
Answer:
(2.4)(10)−4
=20
Step-by-step explanation:
9 are left take 17 and subtract 8
A vertical asymptote is what you get when you try to divide by 0. To find where you get these, you need to look at the denominator and what values of x will make the denominator equal to 0.
In your denominator, you have (x+7)(x-5)(x-3).
What values of x makes (x+7)(x-5)(x-3)=0?
If x = -7, if x = 5, or if x = 3, then that entire expression will equal zero. (Same idea as when you solve equations by factoring.
Now the only place this can get trickier is if one of those factors — one of (x+7), (x-5), or (x-3) — also appears in the numerator. If that happens, then it’s more involved whether you have an asymptote or not. But that doesn’t happen in this example.
So the short version: Asymptotes happen when you try to divide by zero. Dividing by zero is not a good thing. So you just ask yourself, “What will make the denominator 0?”
Yes.
27/51-18/34=0
if something minus something is zero, then the 2 numbers subtracting each other are equal. :)